Gibson paradox: Panel data analysis on ASEAN-T countries - Seçkin Kabak; Tuğçe Dallı (International Econometric Review (IER), 2023)
The existence of a long-term positive relationship between the nominal interest rate and the general price level is called the Gibson paradox in the economics literature. The main purpose of this study is to test whether Gibson paradox is valid for ASEAN-T countries with quarterly data from 1993:Q1 to 2019:Q4 using panel data analysis. In this context, short- and long-term interest rates and consumer price index variables were used. We first examined our data to investigate whether there was a cross-section dependency in our data set. Because of the cross-section dependency in the series, the CADF unit root test, one of the second-generation panel unit root tests, was used. Panel ARDL (Autoregressive Distributed Lag) bounds test was carried out due to the different stationarity levels of the series. According to the panel ARDL bounds test findings, there is a positive relationship between the long-term interest rate and the consumer price index in both the short and long terms. Therefore, the Gibson paradox is valid in ASEAN-T countries in the period under study.
Keywords: E00; E31; E40; 330; Gibson Paradox; Panel Data Analysis; Panel ARDL Bound Test